Effect of the ratio of dietary metabolizable energy to nitrogen content on production performance, serum metabolites, rumen fermentation parameters, and bacterial diversity in yaks - Liu, Xiaojing; Li, Jie; Hao, Lizhuang; Degen, Allan; Wang, Dongyang; Ma, Yonggui; Niu, Jianzhang; Cheng, Yanfen; Liu, Shujie (Frontiers in Microbiology, 2022)
This study examined the effect of the ratio of dietary metabolizable energy (MJ) to nitrogen (g) content (ME: N) on average daily gain (ADG), blood biochemical indices, rumen fermentation parameters and rumen bacterial community in yaks. Thirty-six male yaks, aged 2-3 years, were divided into three groups and received a ME: N ratio of 0.42 (H), 0.36 (M) or 0.32 (L) MJ/g. Dry matter intake ranged between 3.16 and 3.63 kg/d and was lesser (P < 0.001) in the L group than the other two groups. ME intake increased (P < 0.001) with an increase in the ME: N ratio, while N intake did not differ among groups. The ADG was 660 g/d for the M group, which was higher (P < 0.005) than the 430 g/d in the L group, while the H group gained 560 g/d and did not differ from the other two groups. Feed intake to ADG ratio ranged between 5.95 and 7.95, and numerically was highest in the L group and lowest in the M group. In general, the concentration of ruminal total volatile fatty acids (P < 0.03), and molar proportions of propionate (P < 0.04) and butyrate (P < 0.05) increased, while the molar proportion of acetate (P < 0.005) and the acetate: propionate ratio decreased (P < 0.001) with a decrease in the ME: N ratio. Group M had higher ruminal NH3-N content than group H and had a higher serum glucose content but lower urea content, lactate dehydrogenase and creatine kinase content than group L. In ruminal bacteria at the phylum level, the relative abundance of Firmicutes (F) was greater and of Bacteroidetes (B) was lesser, while the F: B ratio was greater in group M than in groups H an L. We concluded that the yaks consuming the diet containing a ME: N ratio of 0.36 MJ/g had the best performance of the three groups.